Population variation of three boobies species (Suliformes:Sulidae) on Gorgona island, Colombian Pacific, linked to sea temperature - Perlaza Gamboa, Alejandro; Giraldo, Alan; Payán, Luis Fernando; Estela, Felipe A. (Revista de Biología Tropical, 2020)
Introduction: Pelagic environment temperature variations may influence population variation of top predators, such as seabirds. Objective: A population response assessment of three species of boobies, in Gorgona Island (Colombian Pacific), in relation to sea surface temperature (SST) variations. Methods: We assessed the relationship between SST variability and monthly abundance of Brown Boobies, Blue-footed Boobies and Peruvian Boobies, in the influence area of Gorgona, the San José region (Peruvian coast) and the Niño 1+2 region. Results: The largest positive correlation was observed between Blue-footed Boobies and Peruvian Boobies with SST at the Niño 1+2 region, with a lag of four and five months, respectively. This delay may correspond to the migration duration from the Peruvian coast to Gorgona. In contrast, Brown Booby abundance decreased as monthly SST in Gorgona increased. Conclusions: These trends may be related to less productivity and prey availability associated with warmer sea surface temperatures. We suggest that SST influences the abundance trend of these three species, and their continuous monitoring will improve our knowledge on the natural variation of these populations.